2022
DOI: 10.1186/s12864-022-08693-4
|View full text |Cite
|
Sign up to set email alerts
|

The GALNS p.P77R variant is a probable Gujarati-Indian founder mutation causing Mucopolysaccharidosis IVA syndrome

Abstract: Background Mucopolysaccharidosis IVA (Morquio syndrome A, MPS IVA) is an autosomal recessive lysosomal storage disorder caused due to biallelic variants in the N-acetylgalactoseamine-6-sulfate sulfatase (GALNS) gene. The mutation spectrum in this condition is determined amongst sub-populations belonging to the north, south and east India geography, however, sub-populations of west Indian origin, especially Gujarati-Indians, are yet to be studied. We aimed to analyse the variants present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Subsequently, low activity of enzyme N ‐acetylgalactosamine 6‐sulphatase in these patients confirmed the diagnosis of MPS IVA. The founder variant p.Pro77Arg in the GALNS gene, previously reported in the Patel community from Gujarat, India, 31 was identified in patient P14. Patients P16–P18 suspected with MPS I, showed mild coarse face, with corneal clouding seen only in patient P17.…”
Section: Resultsmentioning
confidence: 59%
“…Subsequently, low activity of enzyme N ‐acetylgalactosamine 6‐sulphatase in these patients confirmed the diagnosis of MPS IVA. The founder variant p.Pro77Arg in the GALNS gene, previously reported in the Patel community from Gujarat, India, 31 was identified in patient P14. Patients P16–P18 suspected with MPS I, showed mild coarse face, with corneal clouding seen only in patient P17.…”
Section: Resultsmentioning
confidence: 59%
“… 5 , 6 Their study also demonstrated the presence of a founder variant for Tay-Sachs and Morquio-A disease in a particular community of Gujarat, India. 6 , 7 They have also observed a common variant L444P in the GBA1 gene for Gaucher disease patients pan India. 8
Fig.
…”
Section: Introductionmentioning
confidence: 96%
“… 19 A recent study by Sheth and his group has shown the presence of a founder variant P77R in the GALNS gene in MPS IVA patients from Gujarat in a particular ethnicity. 7 Another group of LSDs consisting of Batten disease, Pompe disease, and Fabry disease has a low prevalence in the country. However, in absence of accurate data, the observed low percentages may be due to lack of awareness among clinicians and a dearth of diagnostic facilities across the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation